Installation of pedal-operated alcohol gel dispensers with behavioral nudges and changes in hand hygiene behaviors during the COVID-19 pandemic: a hospital-based quasi-experimental study - Wit Wichaidit; Sommanas Naknual; Nanta Kleangkert; Tippawan Liabsuetrakul (SAGE Publishing, 2020)
We conducted a quasi-experimental study and compared hand hygiene behaviors at potential pathogen transmission events among outpatient visitors (according to structured observations a trained enumerator) before and after installation of 12 pedal-operated alcohol gel dispensers with behavioral nudges (signs attached to the dispensers) at a tertiary hospital in southern Thailand during the COVID-19 pandemic. The enumerator observed 243 events during the pre-intervention period and 223 events during the post-intervention period. Prevalence of hand hygiene was significantly different between the pre-intervention and post-intervention periods (0 vs 24 events, or 0% vs 11%, respectively; p-value <0.001). However, 21 of 24 hand hygiene events were of participants who came from outside the observation area, used the dispensers, then left. Nonetheless, the intervention might have helped to increase access to hand hygiene materials and created opportunities for hand hygiene among hospital visitors in general.